»Four-letters« (γ → ε → β → α) thermal transformation of Si-rich ferrihydrite - Pieczara, Gabriela; Rzepa, Grzegorz; Gaweł, Adam; Tomczyk, Anna (Wydawnictwa AGH, 2015)
Ferrihydrite is a poorly ordered iron (oxyhydr)oxide, ubiquitous in near-surface environments, where it is an important scavenger of numerous toxic metals and metalloids (Cornell & Schwertmann 2003).
Geology, Geophysics & Environment
Keywords: metastable transform; ferrihydrite transform; oxyhydroxide